Physics perspectives and analytics in sports - Prasad N G, Shiva; Harish, V; Ashok , G V (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Fitness, competition, endurance, exercise, and pleasure often spring to mind when we think of sports. Physical education and sports are also quite scientific. It has deep scientific roots. In contemporary sports, performance is demonstrated through science as well as skill, strength, and technique. It is an equally compelling scientific illustration. Sport is influenced in every way by gravity, friction, velocity, and projectile. It encompasses basic laws of Physics in everything from bicycles to tennis rackets, and from high jump to long jump. Understanding the Physics of motion can help athletes move quicker, prevent injuries, plan more effective training sessions, and design aerodynamic equipment and clothes, among other things. Sports and Physics are strongly linked. This is because every sport’s discipline is based on an athlete’s capacity to exert force, and force is one of the fundamental notions in Newton’s laws of motion and other fundamental physics concepts. In this paper the concepts of work, energy, angular momentum, friction, aerodynamics and applications of laws of Physics in various sports activities like tennis, basketball, swimming, skating, surface sports etc. are discussed.